ANALISIS PERUBAHAN POLITIK LUAR NEGERI SRI LANKA TERHADAP TIONGKOK PADA MASA PEMERINTAHAN PRESIDEN MAHINDA RAJAPAKSA - Utami Arti, Ida Ayu Bulan; Priadarsini, Ni Wayan Rainy; Widya Nugraha, A.A Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2021): Jurnal DIKSHI, 2021)
The event of Mahinda Rajapaksa elected as a president affected Sri Lanka’s foreign policy towards Tiongkok. Historically, Sri Lanka has a very strong foreign policy compass oriented towards the Western countries in political, economic and military sectors. However, during the presidency of Mahinda Rajapaksa in 2005 - 2015, Sri Lanka showed a shift in their political orientation by building a closer relationship with Tiongkok in various sectors and limiting their contact with the old Western allies. This research is written to find and describe all of the factors that influenced the foreign political shift of Sri Lanka towards Tiongkok during the presidential era of Mahinda Rajapaksa. The writer of this research uses Theory Determinants of Foreign Policy by William D. Coplin. Keywords: Determinants of Foreign Policy, Sri Lanka, Tiongkok, Mahinda Rajapaksa